Celoso Enterprise / Muhammad Akid Zulkifili ... [et al.] - Zulkifili, Muhammad Akid; Nordin, Muhammad Ghazi Arif; Hamidi, Muhammad Danial; Ahmad, Muhammad Hashim Aiman; Azmi, Muhammad Afiq (2019)
The business is based in a partnership where it consists of five members who hold important roles and positions which are General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital amounts to RM 82,860 where the contribution of each member is RM 10,000 and the rest are RM 40,00 which are acquiredfrom a loan. AKIRA delivers a service that is rarely found not only in the premise's area, Taman Kempas lndah, but also in the whole Malaysia. We manufacture shoe soles that are made from the best of materials, namely Polyurethane Solid, Polyurethane Cellular, and Vulcanized rubber. These raw materials are widely known for its durability and characteristics to withstand differentcircumstances that a shoe sole had to face on a daily basis. Our company will initialize its operation at Jalan Kempas, 1/1, Taman Kempas Indah, 81300, Johor and expand the business further in the future. We also provide sole-replacement service to the customers to help the society dismiss the habit of throwing away their possessions despite the cost that they spent on the item. In order to make the customers more attracted into using our service, they are allowed to customize the designs of the soles according to their preferences. Therefore, our designs are unlimited as customers have a wide selection of designs that come from both the company's artistry and their own creative ideas. AKIRA's employees will also undergo an intensive training before being employed to ensure that they can deliver A 1 services to the customers as an alternative to induce a healthy and constructive relationship with the customers. With the aim of becoming a brand known in the global footwear industry, we will start by introducing this product to the public and maintain potential customers by perpetuating good relationship between the suppliers, creditor and most importantly the customers. From that, our business will run smoothly because no further complications are to arise that can disrupt the flow of the business. With the loan of RM 40,000 as a financial help, we are wishing and hoping to make AKIRA achieve an outstanding and extreme demands from our customers. Our business is to expected to commence on 25th of December in the year 2019 and our vision is to make our company wellknown, established, and satisfied by the customers in order to bring our company to even greater heights. This will be seen by the full cooperation and efforts among the partners to promote the company.